Dilematisasi Pemberian Remisi Bagi Narapidana? Formulasi Berdasarkan Studi Perbandingan Inggris, Irlandia, dan Kanada - Zainudin Hasan; Julian Chandra Adi Pratama (International Forum of Researchers and Lecturers, 2024)
As a country with an overcapacity prison composition of 265,897 people, Indonesia ranks seventh with the most prisoners in the world. In response to this, the government has made several efforts to reduce the density of prisoners, one of which is by providing remissions. However, granting remissions is actually seen as less effective and actually creates differences in the development process in Correctional Institutions (Lapas). Another problem is how to overcome the dilemma of granting remission to prisoners from the perspective of the national legal system. The research method used in this research is a juridical-normative research method with descriptive analytical research specifications which analytically describe the applicable laws and regulations both at home and abroad and legal theories linked to research problems. Analysis of legal materials uses qualitative juridical analysis. The results of this research indicate that the background to the policy of granting remissions to prisoners needs to be tightened so that it can fulfill a sense of justice for society. Apart from that, regarding the policy of granting remissions to prisoners, it is necessary to consider the legal framework of similar policies implemented in England, Ireland or Canada because the tightening of remissions in these countries has resulted in not all prisoners getting remissions or parole.